Jak náboženství ovlivňuje rodinný život? Rozdíly v chování a postojích k rodině mezi českými věřícími a nevěřícími - Nešporová, Olga (Lidé města, 2010)
Religion forms society in a significant way and provides the basic norms of social behaviour. Even if in present-day Czech society almost two-thirds of the population does not belong to any religious denomination, one cannot deny that this society still relates to Christian normas and values. This can be distinctly observed in the family sphere, which is made up of a monogamous marriage and has usually still has a patriarchal structure. Attitudes on families and familial behaviour have, however, changed in this secular society. The article observes, on the basis of data from Generations and Gender Survey (2005), how significant the differences between Roman Catholics and non-believers are today in the sphere of familial behaviour and shared norms. Doing so, it takes into account the influence of age, comparing the reproductive and post-reproductive age categories. It is shown that the differences are not very marked, and are more significant on the level of attitudes, where Roman Catholics defend a more conservative view of family structures, as well as they value marriage and family ties more. However, these beliefs are in contrast with their actual behaviour; which, in comparison to the behaviour of non-believers differs to a lesser degree. Observations suggest that Catholics do not live in relationships without marriage as often, they marry at a younger age, have childer earlier and do not divorce as often. But differences in familial behaviour are rather subtle, more visible in younger generations in comparison to older ones. As for the Czech family, then, actual behaviour changes more quickly than the declared attitudes, which are still quite conservative.